$\newcommand{\R}{\mathbb{R}}
\newcommand{\tto}{\underset{\text{onto}}\to}$
Let us answer the reformulated question: given a convex function $g\colon C\to\R$, when is it possible to find a decreasing convex function $\phi\colon\R\to\R$ such that
\begin{equation}
\phi\circ(-\phi^{-1})=g? \tag{1}
\end{equation}
Here $C$ is a convex subset of $\R$, that is, an interval with some endpoints $c$ and $d$ such that $-\infty\le c<d\le\infty$ (excluding the trivial case when $c=d$).

First here, note that any convex function from $\R$ to $\R$ is continuous. So, the generalized inverse $\psi:=\phi^{-1}$ of a decreasing convex function $\phi\colon\R\to\R$ is just a regular inverse, and the function $\psi=\phi^{-1}$ is also decreasing and convex.

Also, (1) implies that $\psi=\phi^{-1}$ is defined only on $C$, so that we may write $\phi\colon\R\tto C$ (rather than $\phi\colon\R\to\R$) and $\psi=\phi^{-1}\colon C\tto\R$, where $\tto$ means that the map is onto. So, again in view of (1), we may write

\begin{equation}
g=\phi\circ(-\phi^{-1})\colon C\tto C. \tag{1.00}
\end{equation}
Moreover, because the function $\phi\colon\R\tto C$ is decreasing and convex, we see that necessarily
\begin{equation*}
C=(c,d)\text{ for }d=\infty\text{ and some}\ c\in[-\infty,\infty). \tag{1.0}
\end{equation*}

Next, (1) can be rewritten as
\begin{equation}
\psi\circ g=-\psi, \tag{1a}
\end{equation}
which implies $\psi\circ g\circ g=-\psi\circ g=\psi$ and hence
\begin{equation}
g\circ g=\text{id}_C, \tag{2}
\end{equation}
where $\text{id}_C$ is the identity map of $C$; this simple observation is crucial.

In particular, $g$ is one-to-one. Since $g$ is convex and l.s.c., it follows that $g$ is continuous. Therefore and because $g$ is one-to-one, we see that either $g$ is increasing on $C$ or decreasing on $C$. The convexity of $g$ also implies the existence of the left and right derivatives $g'_-(x)$ and $g'_+(x)$ at any point $x\in(c,d)$.

Consider first the case when $g$ is increasing on $C$. Then the identity $g(g(x))=x$ for $x\in C$ implies $g'_-(g(x))g'_-(x)=1$ and $g'_+(g(x))g'_+(x)=1$ for all $x\in(c,d)$. So, if $g'_-(a)<g'_+(b)$ for some $a$ and $b$ such that $c<a\le b<d$, then $g'_-(g(a))>g'_+(g(b))$, which latter contradicts the convexity of $g$ (which implies that $g'_-(x)\le g'_+(y)$ for all $x$ and $y$ such that $c<x\le y<d$). So, here we have $g'_-(a)=g'_+(b)$ for all $a$ and $b$ such that $c<a\le b<d$.
Thus, if the function $g$ is increasing on $C$, it must be affine. It is then easy to see that the condition $g\circ g=\text{id}_C$ implies $g=\text{id}_C$.
So, in this case the only solution of equation (1a) is $\psi=0$, which is not a decreasing function.

It remains to consider the case when $g\colon C\tto C$ is decreasing and convex. Then $g(c+)=d$ and $g(d+)=c$, and $g$ is a bijection of $C$. Since $g$ is continuous and $c<d$, the equation
\begin{equation}
g(z)=z \tag{3}
\end{equation}
has a unique root $z\in(c,d)$.

Since $g$ is decreasing and convex, we also have $g'_+(g(x))g'_-(x)=1$ for all $x\in(c,d)$. Hence, $g'_+(z)g'_-(z)=1$. Also, $g'_-(z)\le g'_+(z)\le0$. Therefore,
\begin{equation}
g'_-(z)\le-1. \tag{4}
\end{equation}

For $x\in C$, let now
\begin{equation*}
\psi(x):=\left\{
\begin{aligned}
z-x&\text{ if }x\ge z,\\
g(x)-z&\text{ if }x\le z.
\end{aligned}
\right. \tag{5}
\end{equation*}
This definition is valid, because, in view of (3), $z-x=0=g(x)-z$ if $x=z$. Next, $\psi$ is decreasing, since $g$ is decreasing.

Further, $\psi$ is obviously convex on $[z,\infty)\cap C$, and $\psi$ is convex on $(-\infty,z]\cap C$ -- because $g$ is convex. Also, in view of (4), $\psi'_+(z)=-1\ge g'_-(z)=\psi'_-(z)$. So, $\psi$ is convex on $C$.

Moreover, (i) in view of (1.0), $\psi(d-)=\psi(\infty-)=-\infty$ and (ii) in view of (1.00), $\psi(c+)=g(c+)-z=d-z=\infty$, so that $\psi\colon C\tto\R$ and hence
$\phi=\psi^{-1}\colon\R\tto C$.

Finally, recalling that $g$ is decreasing and (2) holds, it is straightforward to check that (1a) holds for the so-defined $\psi$.

Thus, for any l.s.c. convex function $g\colon C\to\R$, the following two conditions are equivalent to each other:

(I) there exists a decreasing convex function $\phi\colon\R\to\R$ such that (1) holds;

(II) $C$ is as in (1.0) and $g$ is a decreasing involution of $C$ -- that is, $g$ is a decreasing bijection of $C$ satisfying condition (2).

One may also note that, if condition (II) holds and if $\psi$ is given by (5), then for $\phi=\psi^{-1}$ and all real $y$ we have
\begin{equation*}
\phi(y)=\left\{
\begin{aligned}
z-y&\text{ if }y\le0,\\
g^{-1}(z+y)&\text{ if }y\ge0.
\end{aligned}
\right.
\end{equation*}